HUBUNGAN PEMBERIAN MAKANAN BERANEKARAGAM DAN ASI EKSLUSIF DENGAN STATUS GIZI BALITA DI PUSKESMAS KEMALARAJA OKU - WACHYU AMELIA (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2015)
The purpose of this research was to know the corellation between feeding diverse and exclusive breastfeeding with the 12-59 months toddler nutritional status at Puskesmas Kemalaraja Ogan Komering Ulu. The method of research this research is an analytic survey research by using a cross sectional design with the chi-square test at the 9 5 % significance level . The population is the mother who came withher 12-59 months toddler. The results showed the proportion of the Toddler with good nutritional status was greater in the toddler giventhe diverse food wellas many as 25 persons (83.3%) while the proportion of children with malnutrition status was greater intoddler given the diverse food lessas many as 9 people(75%)From the test results obtained by chi-square p-value of 0.001 which indicates there is a relationship between feeding diverse with toddler nutritional status. The proportion of children with good nutritional status are at greater toddler that given exclusive breastfeedingas many as2 4 people(80%) while the proportion of children with malnutrition status is greater in toddlers who arenot given exclusive breast feeding as many asl O people(83.3%) ,From the test results of the chi-square statistics test obtained p-valueof O.OOO which indicates there is a relationship between exclusive breast feeding with toddler nutritional status.